2007
DOI: 10.1111/j.1530-0277.2007.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ethanol Exposure During Adolescence Increases Basal Dopamine in the Nucleus Accumbens Septi During Adulthood

Abstract: Together these findings suggest that changes in extracellular DA may be an underlying physiological mechanism in adolescent vulnerability to the rewarding properties of ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 48 publications
7
58
2
Order By: Relevance
“…For example, the connections among rewardrelated subcortical regions, as well as the neurocircuitry connecting the prefrontal cortex and these regions, continue to develop during adolescence (see review in DoremusFitzwater et al (2010)). There is also evidence that chronic ethanol administration during adolescence may alter adult brain functioning (Badanich et al 2007;Sahr et al 2004), which in turn could increase the reward value of ethanol and consequently the risks of alcohol-related problems in adulthood. However, further studies, especially with high ethanol doses, will be required to assess the repercussions in adulthood of an ethanol-induced sensitization that developed during adolescence.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the connections among rewardrelated subcortical regions, as well as the neurocircuitry connecting the prefrontal cortex and these regions, continue to develop during adolescence (see review in DoremusFitzwater et al (2010)). There is also evidence that chronic ethanol administration during adolescence may alter adult brain functioning (Badanich et al 2007;Sahr et al 2004), which in turn could increase the reward value of ethanol and consequently the risks of alcohol-related problems in adulthood. However, further studies, especially with high ethanol doses, will be required to assess the repercussions in adulthood of an ethanol-induced sensitization that developed during adolescence.…”
Section: Discussionmentioning
confidence: 98%
“…Fetal alcohol exposure clearly contributes to physical anomalies in humans 14 and animals. 17 Animal research has shown that repeated alcohol exposure during adolescence induces inflammatory cell death, 26 as well as morphologic and neurochemical changes in the brain that may persist into adulthood, 27,28 although studies have yet to explore whether adults would be less vulnerable to these effects than adolescents. Research with human adolescents indicates that severe AUD is associated with reduced hippocampal volume, 29,30 although these results should not be interpreted as necessarily being causal.…”
Section: Development Itself May Be Altered By Alcohol Exposurementioning
confidence: 99%
“…Multiple studies have indicated that systemic administration of EtOH during adolescence results in higher basal DA levels in the Acb (Badanich et al, 2007;Pascual et al, 2009). Comparable EtOH injections in adolescent and adult rats result in higher basal level of DA in the Acb in adolescent rats (Pascual et al, 2009).…”
Section: Adolescent Etoh Adult Mesolimbic Dopaminementioning
confidence: 99%
“…Adolescent EtOH consumption (Sahr et al, 2004), as well as peripheral EtOH injections (Badanich et al, 2007), can increase basal DA levels or DA reuptake in the Acb shell (AcbSh) during adulthood. Similar results are not produced in adult rats with comparable EtOH exposure paradigms (Pascual et al, 2009).…”
Section: Introductionmentioning
confidence: 99%